1989
DOI: 10.1111/j.1365-2427.1989.tb01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of emergence of males and females of Ephoron shigae (Ephemeroptera: Polymitarcyidae)

Abstract: 1. The winged adults of E/j/iomn^/iigfle swarming overlhe water surface were collected by successive random sweeps during their daily emergence period, and the changes in sex and stage composition were examined, in the lower reach of the Asahi River in western Japan.2. The emergence occurred mainly during a 1 ' /2 h period beginning some time after sunset. Male sub-imagos emerged synchronously and moulted to imagos in a 25 min period immediately prior to an abrupt increase of female emergence.3. This timing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…In the bisexual population, the females that were collected some time after emergence were treated as mated individuals. In a previous studies of this mayfly (Watanabe et al 1989;Watanabe 1996), it was revealed that males generally emerged earlier than females, that emerging females were caught at once by males and formed pairs, and that the mating rate of females in the period following the emergence of most of the males, i.e., at the latter half of the mass emergence, reached almost 100%. In our field research on the bisexual population (Asahi-gawa River, Okayama Prefecture; Abukuma-gawa River, Fukushima Prefecture; and Hino-yousui, Tokyo Prefecture), a similar pattern was observed.…”
Section: Distribution and Sex Ratio Of Ephoron Shigaementioning
confidence: 97%
“…In the bisexual population, the females that were collected some time after emergence were treated as mated individuals. In a previous studies of this mayfly (Watanabe et al 1989;Watanabe 1996), it was revealed that males generally emerged earlier than females, that emerging females were caught at once by males and formed pairs, and that the mating rate of females in the period following the emergence of most of the males, i.e., at the latter half of the mass emergence, reached almost 100%. In our field research on the bisexual population (Asahi-gawa River, Okayama Prefecture; Abukuma-gawa River, Fukushima Prefecture; and Hino-yousui, Tokyo Prefecture), a similar pattern was observed.…”
Section: Distribution and Sex Ratio Of Ephoron Shigaementioning
confidence: 97%
“…Protandry has been reported for many species of aquatic insects including mayflies (e.g. Thew 1958;Watanabe et al 1989;Takemon 1990c) and is probably linked to the longer life span of males. In this respect, the habit of drinking water seems to be of particular importance in males.…”
Section: A D U L T Longevity In Relation To M a T I N G And Ovipositimentioning
confidence: 99%
“…Indeed, species such as Ephoron album (Crass 1947;Thew 1958;Britt 1962), Ephoron ladogensis (Tiensuu 1935) and Ephoron shigae (Shioyama 1978;Watanabe et al 1989) are known to die within a few hours of emergence. On the other hand, long-lived ovoviviparous females are also known; for example, Cloeon sp.…”
Section: A D U L T Longevity In Relation To M a T I N G And Ovipositimentioning
confidence: 99%
“…They circulate water through the burrow by moving their tracheal gills. Ephoron adults emerge simultaneously, and often swarm in large numbers (Edmunds et al ., ; Watanabe, Yoshitaka & Mori, ; Cid, Ibanez & Prat, ). After emergence, male subadults (subimagos) immediately moult to enter the adult phase; however, female subimagos mate in flight and do not moult (Brittain, ).…”
Section: Introductionmentioning
confidence: 99%